A narrative review of personalized musculoskeletal modeling using the physiome and musculoskeletal atlas projects - Fernandez, J.; Shim, V.; Schneider, M.; Choisne, J.; Handsfield, G.; Yeung, T.; Zhang, J.; Hunter, P.; Besier, T. (Journal of Applied Biomechanics, 2023)
In this narrative review, we explore developments in the field of computational musculoskeletal model personalization using the Physiome and Musculoskeletal Atlas Projects. Model geometry personalization; statistical shape modeling; and its impact on segmentation, classification, and model creation are explored. Examples include the trapeziometacarpal and tibiofemoral joints, Achilles tendon, gastrocnemius muscle, and pediatric lower limb bones. Finally, a more general approach to model personalization is discussed based on the idea of multiscale personalization called scaffolds.